Evaluasi Pencegahan Pengendalian Infeksi pada Tenaga Kesehatan di RSKD Ibu dan Anak Pertiwi - Ekawaty, Dian; Windarti, Sriyani; Safitri, Helma Liana; Fadli, Andi Muhammad (Jurnal Abdimas Jatibara, 2026)
Infection Prevention and Control (IPC) in the National Hospital Accreditation Standards (STARKES) aims to reduce the risk of infection in healthcare workers, patients, and visitors. The WHO recorded more than 722,000 hospital-acquired infections in 2014, with the incidence in Indonesia reaching 15.74%. Nosocomial infections remain high in Southeast Asia, posing a serious threat to the quality of healthcare services. Furthermore, hospitals, as producers of medical waste, risk environmental pollution if not managed properly. The Objectives to providing information and training related to Infection Prevention and Control at  RSKD Ibu dan Anak Pertiwi Makassar. The method assists health workers, such as providing counseling and in-house training related to infection control prevention, assisted by the PPI team from RSKD Ibu dan Anak Pertiwi. The results of this training show that employees at RSKD Ibu dan Anak Pertiwi have knowledge about PPI, but monitoring and reporting still need to be improved so that those exposed to HAI infections receive better treatment. Nosocomial infections remain common, and IPC programs are not yet optimally implemented. Training is good, but understanding and implementation still need to be improved